Airports for people proceedings of the 8th World Airports Conference organized by the Institution of Civil Engineers, and held in London on 2-5 June 1987. (Thomas Telford, 1988)
Sessions at this conference are headed: Defining passenger needs; COmparisons of different airports and design trends in aircraft development; Gatwick Airport and the rapid rail link; and STOL-ports.